The effect of competence, independence, and motivation on the quality of local government internal audit in regional financial supervision at the East Java Provincial Inspectorate - Silitonga, Anna Dewi Debora; Sundjoto, Sundjoto; Rahayu, Sri (Universitas Wiralodra, 2024)
This research investigates the influence of competence, independence and motivation on the quality of internal audits carried out by the East Java Provincial Inspectorate in the context of regional financial supervision. This study uses a quantitative approach. The population in this study was all 53 East Java Province Inspectorate auditors. Sampling in this research was a total sampling technique. The data collection method used in this research is by using a questionnaire. The data analysis technique in this research is regression analysis. This research finds a significant and positive influence of competence on internal audit quality, indicating that a higher level of competence among auditors contributes to more effective financial supervision. Independence also shows a positive and significant influence on audit quality, emphasizing the importance of auditor impartiality and autonomy in ensuring a rigorous audit of financial processes. Additionally, motivation shows a positive and significant impact on audit quality, underscoring the role of intrinsic drive in driving a proactive and holistic approach to financial oversight. These findings highlight the interaction of these factors in improving the effectiveness of internal audit in the East Java Provincial Inspectorate, explaining important dimensions that contribute to the overall quality of regional financial supervision practices. This research can contribute to academic literature in the field of internal audit, especially in the context of local government.